2018
DOI: 10.4103/ortho.ijortho_188_17
|View full text |Cite
|
Sign up to set email alerts
|

Gait Analysis in Patients with Wide Resection and Endoprosthesis Replacement Around the Knee

Abstract: Background:Limb salvage surgery with endoprosthesis for bone tumor around the knee is reported to have good functional and oncological outcomes. However, the functional assessment using musculoskeletal tumor society (MSTS) and Toronto extremity scoring system remains subjective. We performed gait analysis as an objective assessment of their functional outcome.Materials and Methods:Gait analysis was performed in 20 patients with endoprosthesis replacement around the knee. The temporal parameters assessed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The five-year survival rate is 60% [ 1 ]. Improved survival rates, surgical techniques, and the young age of patients affected by this disease have over time attracted growing interest in the functional outcome and quality of life (QoL) after surgery [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The five-year survival rate is 60% [ 1 ]. Improved survival rates, surgical techniques, and the young age of patients affected by this disease have over time attracted growing interest in the functional outcome and quality of life (QoL) after surgery [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen studies reported the outcomes of walking, function, balance, or strength in participants following surgery at the knee (n = 199) 26–28,30,35,39,41–49,53,54. Seven studies (n = 37) observed the use of walking aids to ambulate 28,35,41–43,46,48.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies reported the outcomes of walking, function, balance, or strength in participants following surgery at the knee (n = 199). [26][27][28]30,35,39,[41][42][43][44][45][46][47][48][49]53,54 Seven studies (n = 37) observed the use of walking aids to ambulate. 28,35,[41][42][43]46,48 Eighty-nine percent of participants were able to ambulate without an aid (n = 33), 11% of participants required 1 to 2 crutches or sticks (n = 4) with this measured between 0.6 and 20.1 years post-surgery.…”
Section: Outcomes In Participants With Surgery Involving the Kneementioning
confidence: 99%
“…Gait analysis as a reliable tool to assess the effectiveness of lower limb surgery for bone neoplasms have been proposed in several studies, especially in populations who underwent prosthetic reconstructions. 23 , 24 This is the first meta-analysis that attempts to depict the effectiveness of rotationplasty for lower limb tumours regarding gait parameters measured by gait analysis. The results of this article suggest that rotationplasty affects all the gait parameters, and summarizes the mean differences compared to the gait of healthy individuals.…”
Section: Discussionmentioning
confidence: 99%